Improving student achievement: incorporating weekly individual practice time in the advanced middle school orchestra classroom - McCready, Daniel (My University, 2025)
The lessons demonstrated in this report are focused on exploring the impact of incorporating student practice time during large ensemble class time in the advanced middle school orchestra. Students have been taking on increasingly numerous activities, family responsibilities, and other pursuits outside the school day and I aim to show that by incorporating one or two “Practice Classes” into the weekly schedule can over time, ultimately benefit student achievement. I have designed these lessons around ideas learned in my Master’s studies in the area of human development and cognition, instrument pedagogy, and classroom management. By incorporating these “Practice Classes” into our weekly schedule over the course of 4 months, we were able to learn several pieces of music more difficult than prior. Furthermore, I was able to attend to some of the lowest achieving students’ needs and bring their level up drastically as a result. The final aspect was that for a majority of students in my specific classroom they are not able to take their instrument home, for any reason, due to location, size of instrument, family dynamics, homelessness, or transportation. From the skills learned in the classes mentioned above, I also created handouts with helpful practice tips, reminders, encouraging phrases, and places for students to write short and long-term goals for themselves. By encouraging the students to practice amongst each other, I have seen a great increase in their willingness to let their guard down, speak up for themselves and their engagement during regular large ensemble rehearsals. At the completion of the activity, I interviewed my students and the use of “Practice Classes” effectively eliminated all of those barriers for the students who are affected by them the most and in the case of the highest achievers, they were able to learn more solo literature during their home practice sessions.
Keywords: Orchestra; Practice; Achievement; Middle school; Middle-school